INCREASING BRAND LOYALTY THROUGH SOCIAL MEDIA MARKETING AND BRAND AWARENESS (SAMSUNG CASE STUDY) - Febrianti, R. Adjeng Mariana; Kusriyantini, Diyanti; Safitri, Febrina Ayuna; Roespinoedji, Djoko (CENTRAL ASIA AND THE CAUCASUS, 2022)
The development of the digital world today has given different nuances in various aspects, especially in business. Companies are competing to compete in order to increase their sales. Currently, social media has become a tool in conducting promotions, making it easier for companies to carry out their activities. This study aims to examine the effect of social media marketing activities and Brand Awareness on Brand loyalty on Samsung Smartphone products. The research population consists of consumers who actively follow five brands with the highest social scores according to social media brand performance data. In this study, quantitative methods were used and research data were obtained through online questionnaires distributed on social media as many as 200 respondents. Based on the results of testing the coefficient of determination for the Social media marketing variable, it was obtained at 42.38% while the coefficient of determination for the Brand Awareness variable was 66.58%. This shows that the two variables have a strong relationship, especially in the variable Brand awareness of Brand Loyalty. The limitation of this study is that the respondents are limited to only in the city of Bandung. This study also provides several recommendations, namely; (1) companies must be selective in choosing which social media is right for the intended target. (2) the company must provide continuous information about the product so that consumers do not seek information from other e- commerce via social media.